Морфологические изменения надпочечных желез при хронической свинцовой интоксикации и корригировании альфа-токоферолом - Озерова, Н.Ю.; Лазарев, К.Л. (Таврический медико-биологический вестник, 2012)
В експерименті на мишах-самцях лiнii BALB/с вивчали характер морфологiчних змiн надниркових залоз при хронiчній свинцевій iнтоксикацii. Встановленi морфологiчнi ознаки порушення морфогенезу та гемодiнамiки, гiдропiчнi та некротичнi змiни клiтин паренхiми та зріст пролiферативної активності фiбробластiв. Альфа-токоферол у помiрному ступені зменшує вказанi процеси. The investigation is devoted to revealing and studing of the morphofunctional changes of suprarenal gland on lead treated male-mice of second generation of BALB/c line. It is experimentally established that the chronic lead intoxication results in dystrophic and necrotic changes of parenchyme cells, disturbance of the hemodynamic and morphogenesis, activation of the fibroblasts. Diminishing of destructive changes due to
administration of alpha-tocopherol was proved.